Use of soy isoflavones as alternative to hormone replacement therapy (HRT) for women in menopause - Edefuhr, Jenny (2007)
The loss of estrogen following menopause can have several effects, including reduction of bone mass, menopausal symptoms, such as hot flushes, decreased cognitive function, vaginal atrophy, and hypercholesterolemia. Traditional treatment of menopausal symptoms using hormone replacement therapy is associated with an increased risk of breast- and endometrial cancer, as well as an increased risk of cardiovascular disease. Daidzein, genistein and glycitein are isoflavones found in great amounts in soybeans, and soybean products. Isoflavones are phytoestrogens, or plant estrogens, that may be classed as natural selective estrogen receptor modulators (SERMs). They exert estrogenic effects (e.g. on bone and plasma lipids) and antiestrogenic effects or no effect on tissues where estrogen stimulation may be undesirable (e.g. breast and endometrium). The current evidence indicates that there are few risks and many potential health benefits for women in menopause to increase their intakes of isoflavones. The effects of isoflavones may be affected by the ability to produce equol. Treating menopausal symptoms via increasing intakes of isoflavones may provide an important alternative to the traditional hormone replacement therapy. Although long-term intervention studies needs to be done before definitive conclusions can be drawn, whether soy isoflavones alone can serve as a safe and effective alternative to hormone replacement therapy. The main objective of this master thesis was to investigate the effects of isoflavones in women during menopause on the menopausal symptoms, bone mass, breast, endometrium, and cardiovascular disease risk by reviewing current literature in the area.